The opioid methadone induces a local anaesthetic-like inhibition of the cardiac Na? channel, Na(v)1.5 - Schulze, V.; Stoetzer, C.; O'Reilly, A. O.; Eberhardt, E.; Foadi, N.; Ahrens, J.; Wegner, F.; Lampert, Angelika; De La Roche, J.; Leffler, A. (British Journal of Pharmacology, 2014)
Treatment with methadone is associated with severe cardiac arrhythmias, a side effect that seems to result from an inhibition of cardiac hERG K? channels. However, several other opioids are inhibitors of voltage-gated Na? channels. Considering the common assumption that an inhibition of the cardiac Na? channel Na(v)1.5, is the primary mechanism for local anaesthetic (LA)-induced cardiotoxicity, we hypothesized that methadone has LA-like properties leading to a modulation of Na(v)1.5 channels.The whole-cell patch clamp technique was applied to investigate the effects of methadone on wild-type and mutant human Na(v)1.5 channels expressed in HEK293 cells. A homology model of human Na(v)1.5 channels was used to perform automated ligand-docking studies.Methadone inhibited Na(v)1.5 channels in a state-dependent manner, that is, tonic block was stronger with inactivated channels than with resting channels and a use-dependent block at 10 Hz. Methadone induced a concentration-dependent shift of the voltage dependency of both fast and slow inactivation towards more hyperpolarized potentials, and impaired recovery from fast and slow inactivation. The LA-insensitive mutants N406K and F1760A exhibited reduced tonic and use-dependent block by methadone, and docking predictions positioned methadone in a cavity that was delimited by the residue F1760. Dextromethadone and levomethadone induced discrete stereo-selective effects on Na(v)1.5 channels.Methadone interacted with the LA-binding site to inhibit Na(v)1.5 channels. Our data suggest that these channels are a hitherto unrecognized molecular component contributing to cardiac arrhythmias induced by methadone.
EVALuna2:2449